Diet restriction and exercise alleviate cognitive reduction of high fat diet (HFD)-induced obese mice by rescuing inflammation-mediated compromised insulin signaling pathway through activating AMPK/SIRT1 signal pathway and suppressing TLR4 signal pathway - Hu Zhang; Ye Zhang; Jiling Liang; Jiahang Li; Miao He; Xin Liu; Jielun Huang; Minghui Wang; Jingjing Fan; Ning Chen (Food Science and Human Wellness)
Obesity, caused by excessive energy, leads to body weight gain and various diseases, including cognitive impairment. Current studies suggest that diet restriction such as optimal fasting and regular exercise are crucial for improving cognitive capacity. However, further exploration is needed to understand the specific mechanisms of high fat diet (HFD)-induced cognitive decline in obesity. In the present study, 4-month-old mice were subjected to HFD feeding for 18 weeks, followed by aerobic exercise and high-intensity intermittent exercise, regular diet feeding, and intermittent fasting for 8 weeks, and then used to evaluate cognitive capacity, inflammation, compromised insulin signaling pathway, and apoptosis in hippocampal tissue, as well as AMPK/SIRT1 and TLR4 signal pathways. Obese mice revealed impaired cognitive capacity as compared with mice fed with regular diets. In contrast, aerobic exercise, high-intensity intermittent exercise, regular diet, and intermittent fasting could inhibit apoptosis caused by inflammation-mediated compromised insulin signaling pathway in hippocampal tissues through activating the AMPK/SIRT1 signal pathway and suppressing the TLR4 signal pathway, thereby rescuing the cognitive impairment of obese mice. Therefore, diet restriction and exercise interventions may play a positive role in reverting obesity-induced cognitive impairment.